Instrumen Pasar Keuangan Perusahaan Internasional Sebagai Indikator Pengambilan Keputusan Manajemen Keuangan UMKM - Ninda Rachmawati; Rosi Ani Prayekti (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
International financial management is financial management on the scale of international financial transactions. The principles of international financial management are the same as domestic financial management. The main scope of international financial management decision-making includes investment decisions, funding decisions and dividend policies. The types of transactions handled in international financial management include exports, imports and foreign exchange markets. This field mainly deals with issues related to the monetary interactions of at least two or more countries. International financial management has developed rapidly due to globalization. It helps to understand the basics of all international organizations and maintain balance between them. The international financial system maintains peace among nations. Without solid financial measures, all countries will work in their self-interest. International finance helps with that problem. The existence of an international financial system means that there is a possibility of an international financial crisis. This is where the study of international financial management becomes very important. To know about the international financial crisis, we must understand the nature of the international financial system. Without international financial management, there is a high probability of conflict and, therefore, the resulting chaos, obvious. International finance helps keep international affairs in order.